Environmental Risk Exposure, Risk Perception, Political Ideology and Support for Climate Policy. Issue 4 (2nd October 2017) - Mayer, Adam; Shelley, Tara O'Connor; Chiricos, Ted; Gertz, Marc
ABSTRACT: The degree to which risk perceptions are socially constructed versus the result of actual exposure to risk is highly contested; how risk exposure and risk perception influence policy attitudes is also poorly understood. We examine how personal exposure to risk factors impacts risk perceptions and policy support related to air pollution and climate change. Our selection of risk exposure variables is informed by the "mental models" literature, and we employ an array of variables to capture subjective risk perceptions using novel survey data. We find that exposure to risk does little to predict risk perception and has a small influence on policy support. Overall, our findings lend support to a constructionist understanding of risk perception and support for policies related to environmental risks.